KORELASI KEMAMPUAN MEMBACA AL-QURAN TERHADAP KEDISIPLINAN SISWA KELAS VII DI MTS HASYIM ASY’ARI - Eis Agnestyaning Zahrotul Jannah; Moh Muslim; Imam Safii (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study used a questionnaire method that was distributed to 65 samples of seventh grade students in Mts Hasyim Asy'ari. Based on the results of the descriptive analysis test, the ability to read the Koran of the students of class VII Mts Hasyim Asy'ari has an average value of 36.85 out of a maximum value of 50, it shows that the ability to read the Qur'an Quran of Class VII Mts Hasyim Asy'ari students are in the sufficient category. Although the student discipline has an average value of 37.77 out of a maximum value of 50, it shows that the discipline of class VII students in Mts Hasyim Asy'ari is in the sufficient category. Based on the results of the r-test using Â the product moment formula for coefficient of determination (R squared) analysis, there is an influence of the independent variable, namely the ability to read the Qur'an (x) in the dependent variable, namely the discipline of students in class VII in Mts Hasyim Asy'ari (y) of 8.94%. It shows that there is an influence but it is weak or low, which is 8.94%, of which the rest is influenced by other factors. Therefore, it can be concluded that the presentation of the hypothesis in this study rejects Ho and accepts Ha, that is, there is a correlation between the ability to read the Koran and the student's discipline, which is 8.94%.